Primula luteoflora (Primulaceae), a new species from Sichuan, China - Ju, Wen-Bin; Huang, Qin; Sun, Zhi-Yu; Huang, Wen-Jun; Li, Huai-Cheng; Gao, Xin-Fen (Phytotaxa, 2018)
Primula luteoflora, a new species of Primulaceae from Sichuan, China, is described and illustrated here. It is morphologically assigned to Primula sect. Petiolares subsect. Davidii, characterized by the leaves firmly papery or leathery, with adaxially impressed veins and reticulate veins distinctly raised abaxially. However, the new species is distinguished by its leaf size, number of lateral veins, glabrous scape, number of flowers and yellow flowers.